Provenance of Cambrian–Ordovician Siliciclastic Rocks of Southwestern Iberia: Insights into the Evolution of the North Gondwana Margin - Lopes, Luís (2015)
This study makes a comparison between the populations of detrital zircons of the Cambrian sandstones from the Ossa–Morena Zone (OMZ) and the Ordovician quartzites from the southern domains of the Central Iberian Zone (S-CIZ) to identify the sediment sources during the development of North Gondwana basins (southwestern Iberia). The U–Pb results obtained for the lower Cambrian sandstones of the OMZ show a remarkable similarity to the detrital zircon ages of greywackes from the underlying OMZ Ediacaran basement (the Série Negra succession). However, there is a greater proportion of Cryogenian grains in the Cambrian rocks, whose main sources are: (1) the late Cadomian magmatic arcs (Ediacaran, ca. 635–545 Ma) which also contributed to filling the late Ediacaran basins of the OMZ; and (2) the early Cadomian arcs (Cryogenian, ca. 700–635 Ma). In the Lower Ordovician quartzites of the S-CIZ (the Armorican and Sarnelha formations), the age distribution of detrital zircons overlaps the population of detrital zircons of the underlying S-CIZ Ediacaran basement (the Beiras Group). However, there are some differences in the Sarnelhas quartzites, which have a population of detrital zircons similar to those of the Ediacaran greywackes and Cambrian sandstones of the OMZ. The Cambrian grains found in the Lower Ordovician quartzites fit the ages of magmatism representing the onset of rifting in North Gondwana that is registered in the OMZ but absent from the S-CIZ. The early Ordovician zircon grains are probably related to the magmatic event that preceded the passive margin stage of the Rheic Ocean, and are found in both the CIZ and OMZ.